2007
DOI: 10.1164/rccm.200603-350oc
|View full text |Cite
|
Sign up to set email alerts
|

A Worldwide Perspective of Atypical Pathogens in Community-acquired Pneumonia

Abstract: The significant global presence of atypical pathogens and the better outcomes associated with antimicrobial regimens with atypical coverage support empiric therapy for all hospitalized patients with CAP with a regimen that covers atypical pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
1
12

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(173 citation statements)
references
References 24 publications
7
153
1
12
Order By: Relevance
“…In Table 1, according to CAPO that is based on 4,337 patients: the atypical pathogen detectable rates in North America, Europe, Latin America and Asia/Africa are 22%, 28%, 21% and 20% respectively (22). However, different countries and regions have different atypical detectable rates.…”
Section: Prevalence Of Atypical Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…In Table 1, according to CAPO that is based on 4,337 patients: the atypical pathogen detectable rates in North America, Europe, Latin America and Asia/Africa are 22%, 28%, 21% and 20% respectively (22). However, different countries and regions have different atypical detectable rates.…”
Section: Prevalence Of Atypical Pneumoniamentioning
confidence: 99%
“…A few CAP inpatients develop severe communityacquired pneumonia (SCAP) and require intensive care unit (ICU) treatment. Due to frequent complications and a long hospitalization period, mortality among these patients is high (1)(2)(3). More than 2 million children under age 5 are killed by pneumonia every year world wide, more than AIDS, malaria, and measles combined (4).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to investigate some of the controversies in the field of NHAP, we performed a secondary analysis of the Community-Acquired Pneumonia Organization (CAPO) database 10 to evaluate the frequency of NHAP in hospitalized patients with CAP in different regions of the world and to compare severity, microbial patterns, and outcomes between the two groups of hospitalized subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al identified eight studies reporting the association between the time to initiate antibiotics and patient outcomes. Four out of five retrospective studies reported statistically significant associations between the time to initiate antibiotics and short-term mortality with a 5% to 46% relative risk reduction (7)(8)(9)(10). However, these studies were limited by their retrospective design based on medical records limiting the number of variables available for adjustment.…”
Section: Optimal Time To Antibiotic Initiationmentioning
confidence: 99%